PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN RETENSI KARYAWAN TERHADAP KINERJA KARYAWAN LUKE ARTISAN BAKERY MALANG - Yeny Reza Dwiningsih; Adriani Kala'lembang (CAPITAL: Jurnal Ekonomi dan Manajemen, 2025)
This study focuses on examining the impact of transformational leadership and employee retention on employee performance at Luke Artisan Bakery Malang, a SMEs in the culinary sector. The data analysis results show that neither transformational leadership nor employee retention has a significant effect on employee performanc. This indicates that leadership effectiveness should not be generalized, but adapted to organizational characteristics such as employee education, work culture, and daily operational dynamics. Moreover, high employee retention does not necessarily lead to optimal performance if not supported by work motivation, employee engagement, and adequate development programs. The findings of this study encourage a recommendation for a more contextual leadership approach and adaptive human resource management strategies within the SMEs environment.